Inducible expression of human papillomavirus‐16 L1 capsomeres in the plastomes of Nicotiana tabacum: Transplastomic plants develop normal flowers and pollen. (19th March 2021) - Latif, Sara; Gottschamel, Johanna; Syed, Tahira; Younus, Iqra; Gull, Kehkshan; Sameeullah, Muhammad; Batool, Neelam; Lössl, Andreas Günter; Mariz, Filipe; Müller, Martin; Mirza, Bushra; Waheed, Mohammad Tahir
Abstract: Human papillomavirus type‐16 (HPV‐16) is the major HPV type involved in causing cervical cancer among women. The disease burden is high in developing and underdeveloped countries. Previously, the constitutive expression of HPV‐16 L1 protein led to male sterility in transplastomic tobacco plants. Here, the HPV‐16 L1 gene was expressed in chloroplasts of Nicotiana tabacum under the control of an ethanol‐inducible promoter, trans‐activated by nucleus‐derived signal peptide. Plants containing nuclear component were transformed with transformation vector pEXP‐T7‐L1 by biolistic gun. The transformation and homoplasmic status of transformed plants was verified by polymerase chain reaction and Southern blotting, respectively. Protein was induced by spraying 5% ethanol for 7 consecutive days. The correct folding of L1 protein was confirmed by antigen‐capture ELISA using a conformation‐specific antibody. The L1 protein accumulated up to 3 μg/g of fresh plant material. The L1 protein was further purified using affinity chromatography. All transplastomic plants developed normal flowers and produced viable seeds upon self‐pollination. Pollens also showed completely normal structure under light microscope and scanning electron microscopy. These data confirm the use of the inducible expression as plant‐safe approach for expressing transgenes in plants, especially those genes that cause detrimental effects on plant growth and morphology.